Key antecedents of consumer purchasing behaviour in emerging online retail market - Ni Luh Putu Indiani; Sagung Ningrat Shinta Febriandari (Cogent Business & Management, 2021)
Despite rapid growth in Indonesian e-commerce transactions, the profile is far below its actual potential compared to other Asian countries. It implies a low intention of Indonesians to conduct an online purchase. Therefore, a study that examines key factors that influence online purchase intention becomes necessary. This research aimed to analyse the influence of perceived benefit and perceived risk toward online purchase intention and actual purchase. A survey was conducted to collect data. Respondents were consumers who have bought retail products online. This study received 450 valid samples. Data was analysed using Partial Least Square. The result showed online purchase intention positively and significantly influence actual purchase. Perceived benefit has a positive and significant influence on online purchase intention and actual purchase. Remarkably, perceived risk does not exert a significant influence on online purchase intention and actual purchase. These insignificant relationships are allegedly due to online practices implemented in the marketplace as well as the respondents' characteristics. As managerial implications, it is recommended that online retailers emphasize the benefits of online shopping in their communication material and provide enhanced benefits to online consumers to increase online sales.
Keywords: 650; Online purchase behaviour; perceived benefit; perceived risk; online purchase intention; online purchase